Functions Of The Islamic Education Environment - Asyfa, Siti Aulina; Khoidir, Khoidir; Lubis, Reva Yolanda (Journal of Sustainable Education, 2025)
This study aims to examine and analyze the functions of Islamic education in fostering awareness and responsibility toward environmental preservation. Islamic education not only emphasizes scientific and spiritual aspects but also plays a strategic role in shaping environmental ethics through Qur’anic and Hadith values. The research method used is descriptive qualitative with a library research approach, analyzing classical and contemporary literature related to Islamic education and the environment. Data were obtained from tafsir books, hadith collections, and relevant scholarly works, then analyzed using content analysis techniques. The results show that Islamic education has three main functions regarding the environment: (1) the theological function, which instills the belief that caring for the environment is part of worship; (2) the moral function, which cultivates a sense of responsibility and trust (amanah) toward nature; and (3) the practical function, which encourages the implementation of Islamic values in concrete actions for environmental conservation. In conclusion, Islamic education plays a vital role in developing ecological awareness among the Muslim community through a value-based approach that promotes harmony between humans and nature.